2010
DOI: 10.1007/s12253-010-9287-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tumor Suppressor and Angiogenesis Markers in Prediction of Recurrence of Non Muscle Invasive Bladder Cancer

Abstract: Non muscle invasive bladder cancers recur frequently and identification of biomarkers for predicting recurrence are necessary. The present study evaluated the individual and synergistic effects of tumor suppressor (p53/p21waf1) and angiogenesis [vascular endothelial growth factor (VEGF)/endoglin (CD105)] markers. The study included 90 cases of non muscle invasive bladder cancer. Cell spots were stained with primary antibodies and Flourescein isothiocyanate (FITC). Slides were observed under confocal laser scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The expression level of TSP-1 mRNA was the lowest in individuals with homozygous G allele. As such, the shorter time-to-recurrence in patients with bladder cancer exhibiting a G allele may be attributed to a decreased TSP-1 expression, which has been associated with an increased risk of disease recurrence and a decreased overall survival by promoting tumour neovascularization [17, 18, 34]. Our results partly supported our hypothesis; however, further functional experiments should be conducted to validate the specific mechanism.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The expression level of TSP-1 mRNA was the lowest in individuals with homozygous G allele. As such, the shorter time-to-recurrence in patients with bladder cancer exhibiting a G allele may be attributed to a decreased TSP-1 expression, which has been associated with an increased risk of disease recurrence and a decreased overall survival by promoting tumour neovascularization [17, 18, 34]. Our results partly supported our hypothesis; however, further functional experiments should be conducted to validate the specific mechanism.…”
Section: Discussionsupporting
confidence: 77%
“…Angiogenesis is associated with an increased recurrence risk of bladder cancer [34]. The downregulation of TSP-1 in bladder cancer is considered as a primary factor contributing to specific changes, for instance, from an antiangiogenic to an angiogenic phenotype during cancer development and recurrence [17, 18, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Endoglin is an independent prognostic factor and it correlates with metastatic disease and poor survival. These results were presented by Santos et al [20] and Agrawal et al [21]. Also, an elevated level of endoglin in blood serum, as well as in urine, can be typical of gastric (Salvensen et al [22]) and endometrial cancers (Nikiteas et al [23]).…”
Section: Discussionmentioning
confidence: 54%
“…The expression of endoglin has been previously studied in bladder cancer. 17,18 Santos et al reported that the presence of angiogenesis in tumor urothelium, which was evaluated as the immunoexpression of endoglin, was significantly associated with disease recurrence in patients with pTa and pT1 bladder cancer who underwent transurethral resection of the bladder tumor. Agrawal et al reported that the ratio of p53/endoglin expression was associated with bladder recurrence in pTa and pT1 bladder cancer, but that endoglin alone was not associated with bladder recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Agrawal et al reported that the ratio of p53/endoglin expression was associated with bladder recurrence in pTa and pT1 bladder cancer, but that endoglin alone was not associated with bladder recurrence. 17 MVD in UTUC was also studied through the immunoexpression of CD34, but the results were controversial. 19 MVD assessed by immunoexpression of CD34 was associated with CSS in 55 patients with UTUC.…”
Section: Discussionmentioning
confidence: 99%